Antibacterial Activity of Ethanol Extract of Krokot Herb (Portulaca oleracea L.) against Skin Infection Pathogens: Staphylococcus aureus, Staphylococcus epidermidis, and Propionibacterium acnes - Annisa, Andi Adria (Journal Microbiology Science, 2025)
Purslane (Portulaca oleracea L.), a traditional herb, is rich in various secondary metabolites like flavonoids, phenolics, tannins, and saponins, known for their antibacterial properties. This study evaluates the antibacterial efficacy of ethanol extract of purslane against skin-infecting bacteria. Using the Agar diffusion method, the study tested the extract's activity against Staphylococcus aureus, Staphylococcus epidermidis, and Propionibacterium acnes. The results indicate significant antibacterial activity, with the highest inhibition observed at a 32% concentration, producing inhibition zones of 10.29 mm, 9.05 mm, and 8.59 mm against S. aureus, S. epidermidis, and P. acnes, respectively. These findings suggest that purslane extract could be an effective antibacterial agent for treating skin infections. This study contributes to the understanding of the potential applications of purslane in medical treatments, emphasizing the need for further investigation into its bioactive compounds.